NGHIÊN CỨU ỨNG DỤNG CHỦNG XẠ KHUẨN Streptomyces griseus VTCC 41724 TRONG PHÒNG CHỐNG BỆNH THỐI GỐC LÚA DO VI KHUẨN Dickeya zeae - Nguyễn, Thị Hiếu Thu; Nguyễn, Thị Vân; Nguyễn, Thị Mỹ Lệ; Lại, Tiến Dũng; Nguyễn, Kim Nữ Thảo; Đinh, Thuý Hằng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON APPLICATION OF Streptomyces griseus VTCC 41724 IN CONTROLLING THE RICE FOOT ROT CAUSING BY Dickeya zeae Foot rot disease caused by Dickeya zeae in rice has been recently concerned in Vietnam, though there has not been a specific prevention and treatment measure. Streptomyces griseus strain VTCC 41724 has been previously reported for the antagonistic properties against Dickeya zeae and other plant pathogenic bacteria, it is therefore investigated for the capability of controlling this disease. Thus, the strain is selected for further studies aiming to application in organic rice cultivation. In this study, the appropriate culture conditions for strain VTCC 41724 to grow and release bioactive substances inhibiting D. zeae were determined, i.e. 2M medium, 5 days, 5% inoculum, and shaking at 160 rpm at 30°C. A microbial formulation SGB was created from biomass of strain VTCC 41724 (7.1 ´ 108 CFU/g) and tested for its effectiveness in controlling the foot rot disease caused by Dickeya zeae under net house conditions. The experiment was carried out on Bac Thom No.7 rice variety, applied the SGB formulation in the soil before the seed and during the disease symptoms, has resulted in a protective efficiency as high as 73.56%. In addition, strain Streptomyces griseus VTCC 41724 also showed the antagonistic activity against harmful fungi including Phytophthora capsici, Alternaria sp., Colletotrichum gloeosporioides and Fusarium sp. This preliminary results showed the potential application of actinomycetes in biological control of foot rot caused by D. zeae, and other microbially mediated plant diseases.